APPLICATION OF E-COMMERCE INFORMATION SYSTEMS IN MIDDLE SMALL BUSINESSES (Case Study: AT THE TAUNA STORE IN TAMBUN) - Tukino; Huda, Baenil; Dwi Lestari, Dina; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The use of information technology is expected to provide great benefits to the increasingly competitive business world in the industrial era 4.0. Businesses that are able to compete in intense competition are businesspeople who are able to implement information technology that is able to improve the quality-of-service excellence. In the industrial era 4.0 the marketing information system underwent a fundamental change marked by the existence of an Electronic Marketing information system or abbreviated as E-Commerce. By using electronic commerce (E-Commerce) can facilitate the marketing of various products or services, both in physical and digital form. Tauna Store, which is engaged in hijab sales, is a UKM that informs the marketing information system into ECommerce that is developed based on web. E-Commerce information systems are built using the PHP programming language using the waterfall method. The results of research conducted at the Tauna Store are able to produce: 1) Increased Sales Turnover on an ongoing basis, 2) Sales services are easily accessible to customers, 3) Transactions conducted by customers can be easily monitored by admin officers and 4) Product information is easily monitored by the owner and admin.